Senzorični sistemi - Meh, Duška (Medicinski razgledi, 1996)
The wealth of energies around us are detected by receptors transducing the physical stimuli in a train of nerve impulses. These are conducted to the perception centres in the CNS, where they elicit sensory impressions. Receptors of the somatosensory apparatus make sensory processing of tactile sensation, proprioception, pain and thermal sensation possible. The character of sensation is determined by the following four stimulus characteristics: modality, intensity, duration and location. The links between physical characteristics of the stimulus and characteristic features of sensory impressions are studied by psychophysical methods.
Keywords: fiziologija; senzorični sistem; receptorji; dražljaji